Estratégias educativas para o autocuidado: percepções de pacientes traqueostomizados - Guermandi, Maísa (2024)
To explore the perception of tracheostomized patients regarding educational strategies for self-care. Methodological process: A descriptive exploratory, qualitative study, conducted after receiving approval from the Human Research Ethics Committee. The study population consisted of patients treated at the Amaral Carvalho Hospital (HAC) who underwent a tracheostomy procedure during the data collection period between August 2023 and March 2024 and were scheduled for an outpatient follow-up visit. The main researcher recruited participants by making daily contact with the nursing team at the institution's Surgical Center to obtain information about the surgical schedule. When a discharge plan was identified for a tracheostomized patient, they were invited to voluntarily participate in the study. The study was conducted in three phases: Phase 1: A semi-structured interview was conducted, followed by a pre training session with an expositive-dialogued class; Phase 2: Educational strategies were implemented, with participants randomized into two groups: the "folder group," trained using the institution's traditional printed folder, and the "skills training group," trained in simulated skills; Phase 3: A semi-structured interview was conducted during the outpatient follow-up visit. The interviews were audio-recorded, and patients were offered breaks of 10 to 15 minutes as needed. The collected information from the interviews was analyzed using the Thematic Analysis technique. Results and discussions: Participants reported relief after the tracheostomy procedure due to improved breathing. However, fear, changes in body image, and apprehension about self-care were also common. Participants valued both the folder and skills training educational strategies but felt insecure about cleaning the cannula at home. The use of educational strategies shows promise in engaging patients in self-care, but health professionals must be adept at identifying and integrating these resources into their practice to meet individual needs and contexts. Conclusion: Regardless of the educational strategy used, there was a low incidence of participants who felt genuinely motivated and confident to implement self-care. A more in-depth evaluation of the variables affecting individuals' motivation and safety in self-care is recommended to develop new and effective strategies.